2015
DOI: 10.1007/s00122-015-2566-1
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations

Abstract: QTLs for delayed canopy wilting from five soybean populations were projected onto the consensus map to identify eight QTL clusters that had QTLs from at least two independent populations. Quantitative trait loci (QTLs) for canopy wilting were identified in five recombinant inbred line (RIL) populations, 93705 KS4895 × Jackson, 08705 KS4895 × Jackson, KS4895 × PI 424140, A5959 × PI 416937, and Benning × PI 416937 in a total of 15 site-years. For most environments, heritability of canopy wilting ranged from 0.65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 59 publications
(95 reference statements)
4
58
0
2
Order By: Relevance
“…The paternal parent of the breeding lines in this research (PI 416937) is slow‐wilting (Abdel‐Haleem et al., ; Hwang et al., ; King et al., ) and has lower radiation use efficiency under water replete conditions relative to fast‐wilting genotypes (Ries et al., ). Consistent with this observation, the mechanism of slow‐wilting in PI 416937 has been attributed to conserving soil moisture prior to a drought (when moisture is abundant) and then drawing upon that moisture during a drought period when fast‐wilting genotypes have already depleted the soil moisture supply (King et al., ; Ries et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The paternal parent of the breeding lines in this research (PI 416937) is slow‐wilting (Abdel‐Haleem et al., ; Hwang et al., ; King et al., ) and has lower radiation use efficiency under water replete conditions relative to fast‐wilting genotypes (Ries et al., ). Consistent with this observation, the mechanism of slow‐wilting in PI 416937 has been attributed to conserving soil moisture prior to a drought (when moisture is abundant) and then drawing upon that moisture during a drought period when fast‐wilting genotypes have already depleted the soil moisture supply (King et al., ; Ries et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…All relative canopy temperature measurements were made before R6 and before there would likely be large decreases in stomatal conductance and transpiration (Secor, Shibles, & Stewart, ) associated with phenology that would impact canopy temperature. Previous research demonstrated that the severity of wilting increases as plants approach maturity (Hwang et al., ). Therefore, it is important to consider possible maturity effects among genotypes as they approach maturity, and there is decreased stomatal conductance, transpiration (Secor et al., ; Wittenbach, Ackerson, Giaquinta, & Herbert, ) and evaporative cooling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al (2007) released two germplasm lines that exhibit improved N fixation during drought stress. Hussein et al (2011), Sinclair et al (2008), Charlson et al (2009), Fletcher et al (2007), Sadok and Sinclair (2010), and Hwang et al (2015) showed that the slow‐wilting trait is associated with multiple mechanisms of drought resistance, including response to atmospheric vapor pressure deficit (VPD), aquaporin activity, and rooting behavior, and genetic analyses have shown that as many as 10 quantitative trait loci (QTL) may be involved.…”
mentioning
confidence: 99%
“…Genotypes evaluated were cultivar A5959, soybean accession PI 416937, and two recombinant inbred lines, 93705-34 and 93705-36, from a cross between cultivars KS4895 and Jackson (Charlson et al, 2009;Hwang et al, 2015). to progressive WD stress.…”
Section: Methodsmentioning
confidence: 99%